If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(3x + -5) + -1(2x + -6) + 1 = -1(12x + 5) + -1(3x + 2) + 3 Reorder the terms: -1(-5 + 3x) + -1(2x + -6) + 1 = -1(12x + 5) + -1(3x + 2) + 3 (-5 * -1 + 3x * -1) + -1(2x + -6) + 1 = -1(12x + 5) + -1(3x + 2) + 3 (5 + -3x) + -1(2x + -6) + 1 = -1(12x + 5) + -1(3x + 2) + 3 Reorder the terms: 5 + -3x + -1(-6 + 2x) + 1 = -1(12x + 5) + -1(3x + 2) + 3 5 + -3x + (-6 * -1 + 2x * -1) + 1 = -1(12x + 5) + -1(3x + 2) + 3 5 + -3x + (6 + -2x) + 1 = -1(12x + 5) + -1(3x + 2) + 3 Reorder the terms: 5 + 6 + 1 + -3x + -2x = -1(12x + 5) + -1(3x + 2) + 3 Combine like terms: 5 + 6 = 11 11 + 1 + -3x + -2x = -1(12x + 5) + -1(3x + 2) + 3 Combine like terms: 11 + 1 = 12 12 + -3x + -2x = -1(12x + 5) + -1(3x + 2) + 3 Combine like terms: -3x + -2x = -5x 12 + -5x = -1(12x + 5) + -1(3x + 2) + 3 Reorder the terms: 12 + -5x = -1(5 + 12x) + -1(3x + 2) + 3 12 + -5x = (5 * -1 + 12x * -1) + -1(3x + 2) + 3 12 + -5x = (-5 + -12x) + -1(3x + 2) + 3 Reorder the terms: 12 + -5x = -5 + -12x + -1(2 + 3x) + 3 12 + -5x = -5 + -12x + (2 * -1 + 3x * -1) + 3 12 + -5x = -5 + -12x + (-2 + -3x) + 3 Reorder the terms: 12 + -5x = -5 + -2 + 3 + -12x + -3x Combine like terms: -5 + -2 = -7 12 + -5x = -7 + 3 + -12x + -3x Combine like terms: -7 + 3 = -4 12 + -5x = -4 + -12x + -3x Combine like terms: -12x + -3x = -15x 12 + -5x = -4 + -15x Solving 12 + -5x = -4 + -15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '15x' to each side of the equation. 12 + -5x + 15x = -4 + -15x + 15x Combine like terms: -5x + 15x = 10x 12 + 10x = -4 + -15x + 15x Combine like terms: -15x + 15x = 0 12 + 10x = -4 + 0 12 + 10x = -4 Add '-12' to each side of the equation. 12 + -12 + 10x = -4 + -12 Combine like terms: 12 + -12 = 0 0 + 10x = -4 + -12 10x = -4 + -12 Combine like terms: -4 + -12 = -16 10x = -16 Divide each side by '10'. x = -1.6 Simplifying x = -1.6
| 7.68x+4=58.9824+2x | | -7u=-28 | | (4-9x)(2-5x)=0 | | b-a=-5 | | m^2+9=73 | | 8.8a+14=119.6 | | s-5=25.58 | | 90+b=a | | 1-5v+7v=-27 | | 2.32x+11.6=23.2 | | -27=1+x+6x | | -7x=-5+15x-(-x-5) | | -3=14-11n-6n | | 13n-239=4n-14 | | -7x=-5+15x-(x-5) | | 2(v-6)=4v-16 | | -12q+4=89-6 | | 4+3=223 | | (x-y)-90=0 | | 9(7x+8)+3(x+10)= | | m-12+4m=13 | | 7x-4x=-36 | | 5-7x-8+14x-17=10x-4x-3 | | 6x+8=-37-3x | | 1-3k-13=30 | | 5-7x-8+14x-17=11-2+5+28-10+18 | | 2X^4+3X^3+X^2=0 | | x-y=3*x-y | | -14k-10k=24 | | -2(p+1)=-5-p | | 12=-b-3b | | 5d-7=2-4d |